Roll of thunder, hear my cry - Taylor, Mildred D. (New York : Dial Books, 1976)
A black family living in Mississippi during the Depression of the 1930s is faced with prejudice and discrimination which its children do not understand.
John Newberry Medal
Keywords: African Americans -- Juvenile fiction; Logan family (Fictitious characters : Taylor) -- Fiction; African Americans -- Fiction; Prejudices -- Fiction; Depressions -- Fiction